2014 IEEE International Conference on Power and Energy (PECon) 2014
DOI: 10.1109/pecon.2014.7062443
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fault resistance on the behavior of superconducting fault current limiter in power systems

Abstract: Current limiting behavior of a superconducting fault current limiter (SFCL) depends on the prospective fault current, which in turn depends on fault resistance. Accordingly, this paper introduces a comprehensive study on the effect of fault resistance on the behavior of SFCL in power systems. A model for the system under study and SFCL is developed using PSCAD/EMTDC software. The fault resistance is changed from a very small value (0.5 Ω) to a large value (25 Ω). At each fault resistance, the line currents are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…4 illustrates the output 3-phase current of PMSG before and after applying SFCL. Before applying SFCL, the current increased instantaneously on all phases with different values depending on the instant of fault for each phase [22]. The maximum fault current occurred on phase b with instantaneous value of 282 A, which represents 220% of the nominal peak current.…”
Section: B Impact Of Sfcl On Pmsg Performancementioning
confidence: 99%
“…4 illustrates the output 3-phase current of PMSG before and after applying SFCL. Before applying SFCL, the current increased instantaneously on all phases with different values depending on the instant of fault for each phase [22]. The maximum fault current occurred on phase b with instantaneous value of 282 A, which represents 220% of the nominal peak current.…”
Section: B Impact Of Sfcl On Pmsg Performancementioning
confidence: 99%
“…Regarding the importance of this parameter and looking at the performed studies that have individually concentrated on the impact of fault resistance and fault distance on the FCRR of SFCL in literatures, a few detailed studies can be found. The author in evaluates the impact of the fault resistance on the current limiting behavior of RSFCL, but fault distance impacts have not been considered in this work. In addition, no mathematical expression has been presented to describe the current limiting behavior of RSFCL.…”
Section: Introductionmentioning
confidence: 99%